Evolutionary quasi-variational inequality for a production economy. (April 2018) - Donato, Maria Bernadette; Milasi, Monica; Vitanza, Carmela
Abstract: This paper is focused on the analysis of a time-dependent general equilibrium problem for a production economy by using the variational inequality approach. More precisely, the time-dependent allocation-price equilibrium consists in searching the optimal allocation by households and firms and in searching the market clearing condition. Firstly, a new formulation of the economic equilibrium problem by means of an evolutionary quasi-variational inequality is proven in the general context of semistrictly quasiconcave utility functions. Finally, an existence result for equilibrium solutions is given.